Orthogonal Analysis of Water Permeability of Pervious Concrete - Li, Zhongyuan; Yang, Jie; Li, Shaobo; Xu, Xinyi; Song, Hanzhi (Asian Journal of Chemistry, 2014)
The development application of pervious concrete is reviewed in this article. The study state of pervious concrete on working performance, mechanical performance, drainage and sound absorption performance is summarized, especially the drainage performance. The paper use orthogonal test and analyze four factors, the types of aggregate, sand rock volume ratio, cement amount and molding pressure to specify the impacts on permeability coefficient of pervious concrete. The experimental results are valued by maximum range and standard deviation to judge the influential degree of each factor. Regression equation and its functional image are imitated to reaffirm the accuracy of the previous judgment.